Clinicopathological study of gastric biopsy in gastritis patients - Raveena Yallur; Mahesh Satapute; Prabhu Mural (Al Ameen Medical College, 2024)
Background: Gastritis is the inflammation of gastric mucosa characterized by morphological and histopathological changes. This study was undertaken mainly to study the histo- morphological features of gastritis patients. Material and Methods: A cross sectional study was conducted in 100 cases of gastric biopsies in a tertiary care hospital in North Karnataka. The biopsies were fixed and sections were made from paraffin blocks. Two slides with three levels in each slide were examined under light microscope stained with Haematoxylin& Eosin and Giemsa. The slides were examined by two pathologists and findings were documented, compiled and analysed using statistical software. Results: This study had shown that 43.0% of the cases had gastric ulcer, 42.0% had chronic gastritis and acute gastritis in 15.0% of the cases. H. Pylori was found in 36.0% of the cases. The histological features included mild, moderate and severe inflammation, neutrophilic activity, mild mucosal atrophy, eosinophilic infiltration, lymphoid follicles and dysplasia. Conclusion: This study had shown morphological changes and histopathological changes along with H Pylori infection in cases with gastritis.